EFFECTS OF PAPAYA LEAF EXTRACT ADMINISTRATION IN CHICKENS: I. DUODENUM PATHOPHYSIOLOGICAL RESPONSE - Mufti Kamaruddin; M Nur Salim (Jurnal Sain Veteriner, 2000)
The pathophysiological effects of papaya leaf extract administration were studied in 20 local-three month-old chickens weighing 577±69.979 g. The chickens were randomly evenly divided into 4 groups. P0 group just orally received one single dose Of 3.0 ml aquadest. The P1 P2 P3 and P4 groups were treated orally with one single dose of 1,5 ml, 2.0ml, 2.5 ml and 3.0 ml papaya leaf extract respectively. The extract was made from 400 g papaya leaves, extracted directly by simple traditional methods. Four days after treatment, the chickens were sacrificed, the duodenum were excised for macroscopic examinations, than fixed in 10% formalin prepared for microscopic examination using paraffin method and routine hematoxylin-eosin staining. The results indicated that pathological duodenum effects occurred in groups P2, P3 and P4. Macroscopically, the duodenum were hyperaemic and haemorrhagic. Microscopically the duodenum of these groups showed erosions of ephitelial mucous cells, hyperaemic and haemorrhagic propia. The P0 and Pt did not show any macroscopic and microscopic changes. It was concluded that one single dose of 3.0 ml aquadest or 1.5 ml of papaya leaf did not cause any pathophysiological effects in duodenum chicken, but a single dose of 2.0 ml, 2.5 ml or 3.0 ml did. The greater the dose the worse the effects.